Professional Ethics in the Commodity Economy - Quoc, Nguyen Anh; Van Y, Nguyen (Edelweiss Applied Science and Technology, 2024)
Research on professional ethics in the conditions of commodity economy aims to clarify the systematic transformation of natural functions into social tasks, thereby clarifying the moral life governed by standards and measured by money; profession is the object of life. The content of the article uses the methodology of humanistic and social philosophy, and combines qualitative methods in the study of moral life, in which humans are both the subject and the object of morality. The result has clarified the object of morality, which is the truth of life. However, the truth of life is standardized and measured by money, causing the truth to be distorted. Profession is joy, the mission of life, the truth, creativity, and freedom in profession, but working for money is suffering; that is, forced labor. The conclusion is that the right to own life in all species is the instinct of survival. Property rights make each individual a product of the family, religion, state, economic unit, and professional organization. Standards are the measure of occupation, and social status in the division of labor becomes the appropriation of money from each other, giving rise to class morality. The struggle is not to abolish humans but to abolish everything that is not human for sustainable development in a commodity economy.